Directionality of Dating Violence Among High School Youth: Rates and Correlates by Gender and Sexual Orientation - Norris, Alyssa L. (Journal of interpersonal violence, 2022)
Sexual minority adolescents are at greater risk for experiencing teen dating violence (TDV) in their dating relationships. Although adolescents in dating relationships often report experiencing and perpetrating various forms of TDV, the directionality of TDV based on youth?s reported gender and sexual orientation is not known. A sample of 10th-grade students (N = 1,622) recruited from high schools in the Northeastern United States completed assessments of TDV victimization and perpetration and reported their past-month heavy alcohol use and marijuana use. Sexual minority girls (58%) and boys (36%) were more likely to experience TDV than heterosexual girls (38%) and boys (25%), respectively. Sexual minority boys were less likely, although the confidence intervals included one, to engage in dual-role physical TDV (odds ratio [OR] = 0.14, 95% confidence interval [CI] [0.00, 1.26]) and threatening TDV (OR = 0.14, 95% CI [0.00, 1.02]), and instead were more likely to be victimized. In contrast, the profiles of TDV were similar for girls, with sexual minority girls only being more likely than heterosexual girls to report dual-role physical TDV (OR = 2.23, 95% CI [1.07, 4.66]). Compared with unidirectional TDV, bidirectional TDV was significantly associated with sexual minority girls? substance use, but not with heterosexual girls? substance use. Sexual minority youth report higher rates of TDV, with sexual minority boys being distinctly at-risk for being victimized within their dating relationships. Engagement in both TDV victimization and perpetration was distinctly associated with substance use for sexual minority girls, highlighting the need for integrated prevention efforts and support.